Formation of self-assembled polymeric complexes with bridged azido-dicarboxylato ligands (Journal of the College of Basic Education, 2022)
In this publication, several six coordinate bridged-polymeric metal complexes are reported. The reaction of 4,4`-dipyridine with ethyl chloroacetate in mole ratio of 1:2 gave the multidentate carboxylate ligand bis(N-carboxylatomethyl)-4,4`-dipyridinium). The reaction of the ligand with metal chloride and sodium azide resulted in the formation of the required polymeric complexes. Upon complex formation, the carboxylato ligand behaves as a neutral multidantate species. The mode of bonding and overall geometry of the complexes were determined through physico-chemical and spectroscopic methods. These studies revealed octahedral geometry about metal centres and complexes of the general formula [Cr2(L)(N3)4]Cl2.H2O, Na2[Ag2(L)(N3)4].H2O and [M2(L)(N3)4].H2O (where M = Mn, Fe, Co, Ni, Cu, Zn and Cd) were reported. These compounds were characterised by 1H, 13C NMR, mass spectroscopy, C.H.N, A.A., chloride content, magnetic susceptibility, melting point and molar conductance. Molecular structure for the complexes has been optimised by CS Chem 3D Ultra Molecular Modelling and Analysis Program and supported the formation of six coordinate polymeric complexes.